Longitudinal Changes of Deep and Surface Learning in a Constructivist Pharmacy Curriculum - Andries S. Koster; Jan D. Vermunt (MDPI AG, 2020)
In the undergraduate Pharmacy program at the department of Pharmaceutical Sciences, Utrecht University, an educational model is used that is aimed at the development of deep and self-regulating learning. It is, however, unknown whether these objectives are realized. The aim of this study was to assess longitudinal changes in processing and regulation strategies of student learning during their progression in the curriculum, that is explicitly based on constructivist principles. Processing strategies (deep vs. stepwise), regulation strategies (self- vs. external), conceptions of learning and orientations to learning were measured with the Inventory of Learning patterns of Students (ILS). Longitudinal data are reported here for students, of which data are available for year 1/2 and year 4/5 (n = 90). The results demonstrate that the use of deep processing (critical thinking in particular, effect size = 0.94), stepwise processing (analyzing in particular, effect size = 0.55) and concrete processing strategies (effect size = 0.78) increases between the bachelor phase (year 1/2) and the master phase (year 4/5). This change is based on the students having a constructivist view about the nature of learning and is mediated through a relatively large increase in the use of self-regulating strategies (effect size = 0.75). We conclude that this six-year undergraduate Pharmacy program effectively stimulates the development of deep and self-regulated learning strategies in pharmacy students.